Science Fictions: How Fraud, Bias, Negligence, and Hype Undermine the Search for Truth by Stuart Ritchie - Bauer, Henry (Journal of Scientific Exploration, 2021)
This book does a splendid job of describing and documenting the dysfunctional features of contemporary science mentioned in the book’s subtitle. Were I still teaching, I would have my students read this book as the basis for many productive class discussions. The margins of my copy overflow with notes, comments, and cues for further reading. The 80 pages of endnotes, for some 260 pages of text, are the best and most interesting documentation that I can recall ever finding in such a book. At any rate, I recommend this book wholeheartedly; I doubt that anyone interested in the nature of contemporary science will fail to be informed and to find stimulation for further thought and reading. The Preface already promises that this will be a page-turner. Many will be astonished and disheartened by the fully documented cases of outwardly distinguished academics whose work was largely or completely fraudulent, as with Diederik Stapel (pp. 4–5 and later). Ritchie quite appropriately sees replication as the essence of science (p. 5): “If it won’t replicate, then it’s hard to describe what you’ve done as scientific at all.” Note that this is an empirical statement, not the Popperian criterion that theories must be falsifiable in principle if they are to be regarded as scientific. If a claimed observable phenomenon cannot be repeated, then we cannot know that it was real, that it happened even once, when first claimed. That’s the continuing dilemma for parapsychology, cryptozoology, for anomalistics in general. Ritchie points out that the scientific community failed to handle appropriately the issue of replication in the case of Stapel, and also with Daryl Bem’s claimed evidence of precognition. Overall, peer review and journal publication practices have not saved science from “a dizzying array of incompetence, delusion, lies, and self-deception” (p. 7).